Coupling behavior of shear deformation and end rotation of elastomeric seismic isolation bearings. (30th September 2016) - Ishii, Ken; Kikuchi, Masaru; Nishimura, Takuya; Black, Cameron J.
Summary: This paper presents a mechanical model for predicting the behavior of elastomeric seismic isolation bearings subject to combined end rotations and shear deformation. The mechanical model consists of a series of axial springs at the top, mid‐height and bottom of the bearing to vertically reproduce asymmetric bending moment distribution in the bearings. The model can take into account end rotations of the bearing, and the overall rotational stiffness includes the effect of the variation of vertical load on the bearing and the imposed shear deformation. Static bending tests under various combinations of vertical load and shear deformation were performed to identify the mechanical characteristics of bearings. The test results indicate that bearing rotational stiffness increases with increasing vertical load but decreases with increasing shear deformation. Simulation analyses were conducted to validate the new mechanical model. The results of analyses using the new model show very good agreement with experimental observations. A series of seismic response analyses were performed to demonstrate the dynamic behavior of top‐of‐column isolated structures, a configuration where the end rotations of isolation bearings are typically expected to be larger. The results suggest that the end rotations of elastomeric bearings used in practical top‐of‐column isolated structures do not reduce the stability limit of isolation system. Copyright © 2016 John Wiley & Sons, Ltd.